Surgical Management of Breast Cancer under Local Anaesthesia: A Surgeon's Perspective (Delta Medical College Journal, 2017)
Background: Treatment of breast cancer without surgery may not be effective. But in elderly patients with lots of co-morbidities, surgical management often cannot be done due to the significant risks of general anesthesia. The need for a safe, easy and effective alternative anaesthetic technique that can provide adequate peroperative analgesia as well as reduced anxiety in such group of patients was the main indication for this study.Materials and method: This prospective study was done on eleven patients, with coexisting medical conditions and who were not at all fit for general anaesthesia, and underwent breast cancer surgery under local anaesthesia. The patients were studied with regard to intraoperative analgesia, haemodynamic stability and complications related to technique. The study was done in Delta Medical College Hospital, Dhaka, Bangladesh.Results: Mean±SD of study patients were 64.7±7 years old and all were suffering from coexisting medical conditions. Following local anaesthesia, mean intraoperative heart rate was 81.5±11.8 beats/min and the mean blood pressure was 127.3/79±9.6/7.0 mmHg. Patients felt no pain after infiltration of local anaesthetics, but experienced it if any place was missed before dissection. No complication occurred due to this procedure. All the candidates were fully satisfied with the procedure.Conclusion: Local anaesthesia provides satisfactory pain control along with keeping haemodynamics stable for surgical treatment of breast cancer among elderly patients having co-morbid conditions.Delta Med Col J. Jul 2017 5(2): 63-67